Vita di un monumento Il Ninfeo di Egeria tra storia e rappresentazione - Cimadomo, Paolo (Forme del disegno, 2023)
"Vita di un monumento" traces the processes of transformation that engaged the so-called Nymphaeum of Egeria in the Caffarella Valley in Rome. The volume begins with the analysis of the historical, geographical, and archaeological background before moving onto an examination of the monument in its current form, from its construction to its reuse and refunctionalisation over time. The text organizes the current documentation and draws attention to the features of the building. After tracing the historical, architectural, and functional development, it highlights the contribution of various virtual representation and reconstruction methodologies and approaches targeted at a thorough study of the Nymphaeum itself. This development aims to portray the process of surveying, developing, and combining heterogeneous data into two- and three-dimensional models, capable of providing a critical interpretation of the monument and facilitating multidisciplinary research. The volume concludes with a selection of the most important graphic representations of the Nymphaeum, dating from the first records to the end of the 19th century. Following the issues discussed within the book, the plates integrate historical and archaeological issues ¬- related to the study of sources of human past - with questions of representation as a tool for knowledge.